Spin-Glass Behaviour and Magnetic Properties of Multi-Metallic Prussian Blue Compound Co0.25Mn1.25[Fe(CN)6]·5.9H2O - Lin, Qing; Huang, Kangling; Huang, Haifu; He, Yun; Xu, Jianmei (Asian Journal of Chemistry, 2014)
Multi-metal prussian blue compound Co0.25Mn1.25[Fe(CN)6]·5.9H2O has been synthesized.The temperature-dependent magnetic susceptibilities indicate that there exist a ferrimagnetic interaction in the compound and magnetic transition at 9.5 K. The Curie constant of C = 6.59 cm3 K mol-1 and Curie temperature of q = -11.28 K were observed in fitting according to Curie-Weiss law. The observed value of coercive field and remanent magnetization at 4 K for the compound are 230 Oe and 0.072 μb. The presence of spin-glass behaviours in the compound is ascribed mainly to domain mobility or domain growth under different cooling conditions.The behaviour of c' and c" is typical of a spin glass statego through a maximum with strong frequency dependence. The observed values for the isomer shift, the quadrupole splitting is 0.41(9) mm/s, I.S. is -0.15(4) mm/s, values which are characteristic of low-spin Fe(III) (S = 1/2) ions. The Mössbauer spectroscopy study revealed the presence of low spin Fe(III) (S = 1/2).